Extracellular DNA in environmental samples: occurrence, extraction, quantification, and impact on microbial biodiversity assessment - Bairoliya, Sakcham (2022)
Environmental DNA, i.e., DNA extracted directly from environmental samples, has been used to understand microbial communities in the environment and to monitor contemporary biodiversity in the conservation context. Environmental DNA often contains both intracellular DNA (iDNA) and extracellular DNA (eDNA). eDNA can persist in the environment and complicate environmental DNA sequencing-based analyses of microbial communities and biodiversity. Although several studies acknowledged the impact of eDNA on DNA-based profiling of environmental communities, eDNA is still being neglected or ignored in most studies dealing with environmental samples. In this article, we summarize key findings on eDNA in environmental samples and discuss the methods used to extract and quantify eDNA as well as the importance of eDNA on the interpretation of experimental results. We then suggested several factors to consider when designing experiments and analyzing data to negate or determine the contribution of eDNA to environmental DNA-based community analyses. This field of research will be driven forward by (i) carefully designing environmental DNA extraction pipelines by taking into consideration technical details in methods for eDNA extraction/removal and membrane-based filtration and concentration; (ii) quantifying eDNA in extracted environmental DNA using multiple methods, including qPCR and fluorescent DNA binding dyes; (iii) carefully interpreting the effect of eDNA on DNA-based community analyses at different taxonomic levels; and (iv) when possible, removing eDNA from environmental samples for DNA-based community analyses.